Characterisation of Au surface properties relevant for UV photoemission-based charge control for space inertial sensors. (9th September 2020) - Olatunde, Taiwo; Apple, Stephen; Inchauspé, Henri; Parry, Samantha; Letson, Benjamin; Wass, Peter J; Mueller, Guido; Conklin, John W
Abstract: Precision space inertial sensors used for satellite geodesy missions, tests of fundamental physics, and gravitational wave observation utilise UV photoemission to control the electric potential of free-falling test masses with respect to their surrounding electrode housings. Successful generation of photoelectrons requires UV light energies greater than the work function of the illuminated surface. To ensure bi-polar test mass charge control (positive and negative charge rates), the quantum yields of the test mass and electrode housing surfaces must be well-balanced. LISA Pathfinder used mercury vapour lamps at 254 nm to discharge the gold coated test mass by likely relying on contaminants to lower the work function of gold from its nominal value of 5.2 eV. The LISA gravitational wave mission plans to use UV light emitting diodes (LEDs) instead of mercury vapour lamps. These UV LEDs have a lower mass, higher power efficiency, and produce light at wavelengths below 240 nm. In this paper, we measure the quantum yields of several Au-coated surfaces over a range of UV wavelengths and environmental conditions, varying temperature, vacuum pressure, and measuring over long periods of time. We use these data to draw conclusions and make recommendations for the development and handling of precision space inertial sensors for LISA and for other missions in the future.